ANALISIS PENGENTASAN KEMISKINAN MELALUI BELANJA LANGSUNG DAN TIDAK LANGSUNG PEMERINTAH KABUPATEN KOTA DI PROVINSI JAWA TIMUR - Kristiyanto, Sony (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2015)
Every country in this world must be facing poverty problem in their economic. There are many ways to reduce poverty problems in each country. One of them is using fiscal policies through government expanditure. In Indonesia’s fiscal policies, there are two types of government expanditure. They are: direct government expanditure and indirect expanditure. This paper study about how both of government expanditure will effect the reduce of poverty in East Java Province. The research is coming into conclusion that both of government expanditure will effect poverty in East Java Province, but in the different way. Direct government expanditure will reduce poverty if the government increase this expanditure. In contrary, indirect government expanditure will raise poverty when it is increasing